FORMING OF COMPREHENSIVE ASSESSMENT INDICATORS OF REMUNERATION SYSTEM’S INFLUENCE ON ENTERPRISE ACTIVITY - Vera L. Zhevnerchuk; Irina A. Varpaeva (Статистика и экономика, 2016)
The article considers the performance indicators of the company, such as labor productivity, product proﬁ tability, proﬁt, cost of production, sales and their relationship withthe system of remuneration. We proposedcomprehensive indicator for evaluation.